Cell‐Type Variation in Stress Responses as a Consequence of Manipulating GRP78 Expression in Neuroectodermal Cells. Issue 3 (March 2015) - Martin, Shaun; Lovat, Penny E.; Redfern, Chris P.F.
ABSTRACT Glucose‐regulated protein 78 (GRP78) is a stress sensor which interacts with unfolded protein response (UPR) activators in the endoplasmic reticulum (ER). The aim of this study was to test the hypothesis that GRP78 has distinct functional roles in mediating the effects of ER stress in neuroblastoma compared to other neuroectodermal cancer types. GRP78 was knocked down or overexpressed in neuroectodermal tumor cell lines. Protein and transcript expression were measured using Western blotting, confocal microscopy, and real‐time polymerase chain reaction; cell stress was assessed by measurement of oxidative stress and accumulation of ubiquitinated proteins and cell response by measurement of apoptosis and cell viability. Neuroblastoma cells were more sensitive to ER stress than melanoma and glioblastoma cells. GRP78 knockdown increased stress sensitivity of melanoma and glioblastoma cells, but not neuroblastoma cells. Over‐expression of GRP78 decreased the stress sensitivity of melanoma and glioblastoma cells but, in contrast, increased the stress sensitivity of neuroblastoma cells by activation of caspase‐3‐independent cell death and substantially increased the expression of UPR activators, particularly inositol‐requiring element 1 (IRE1). The results from this study suggest that cell‐type specific differences in the relationships between GRP78 and the UPR activators, particularly IRE1, may determine differential sensitivity to ER stress. J. Cell. Biochem. 116: 438–449, 2015. © 2014 Wiley Periodicals, Inc.